An inter-laboratory in vitro assessment of cigarettes and next generation nicotine delivery products. (15th October 2019) - Ito, Shigeaki; Taylor, Mark; Mori, Sakura; Thorne, David; Nishino, Tomoki; Breheny, Damien; Gaça, Marianna; Yoshino, Kei; Proctor, Christopher
Highlights: In vitro assays were employed to test extracts derived from cigarette smoke or aerosols from an E-cigarette and two tobacco heating products. Cigarette smoke extract induced significant and dose-dependent induction of cytotoxicity and oxidative stress in epithelial cells. Extracts of next generation nicotine delivery products did not elicit significant responses in epithelial cells. Two laboratories obtained comparable results in support of the assessment of next generation nicotine delivery products with in vitro techniques. Abstract: In vitro testing can facilitate the rapid assessment of next generation nicotine delivery products (NGPs) with comparisons to combustible tobacco products. In vitro assays for cytotoxicity and oxidative stress were employed at BAT (UK) and JT (Japan) to test total particulate matter (TPM) of a scientific reference cigarette and aerosol collected mass (ACM) of a commercially available E-cigarette and two tobacco heating products (THP). 3R4F TPMs were generated using the Health Canada intense (HCI) regimen, a modified regime (mHCI) for the THP ACMs and the CORESTA recommended method no. 81 for the E-cigarette ACM. Human lung cells were exposed to the test product TPM/ACMs at concentrations between 0–200 μg/ml followed by the employment of commercially available assays for endpoint analysis that included reactive oxygen species (ROS) generation, the glutathione ratio (GSH:GSSG), activation of the antioxidant response elements (ARE) and cellular viability. TPM/ACM nicotine concentrations were quantified using a UPLC-PDA technique. At both laboratories the 3R4F TPM induced significant and dose-dependent responses in all in vitro assays, whereas no significant responses could be measured for the NGP ACMs. In conclusion, both laboratories obtained comparable results across all endpoints therefore demonstrating the utility of the in vitro techniques combined with standardised test products to support the assessment of NGPs.